Characterization of the single-cell derived bovine induced pluripotent stem cells. Issue 5 (October 2017) - Zhao, Lixia; Wang, Zixin; Zhang, Jindun; Yang, Jian; Gao, Xuefei; Wu, Baojiang; Zhao, Gaoping; Bao, Siqin; Hu, Shuxiang; Liu, Pentao; Li, Xihe
Highlights: The stable bovine iPSCs discussed here were single cell derived. The efficiency of single bovine iPS cell cloning is 40%. We obtained single cell derived bovine iPSCs by the piggyBac delivery transgenes Oct4, Sox2, Klf4 and cMyc combined with Lif and bFGF culture system. These iPSCs displayed some pluripotent characteristics but not naïve pluripotent. Abstract: Single-cell derived bovine induced pluripotent stem cells (iPSCs) were generated by the introduction of piggyBac transposons with CAG promoting transcription factors ( Oct3/4, Sox2, Klf4 and cMyc ). In the study, the bovine iPSCs colony from single cell could passage more than 50 passages after enzymatic dissociation into single cells. These bovine iPSCs cells kept the normal karyotype and displayed dome shaped clones similar to mouse embryonic stem cells. They showed pluripotency in many ways, including their expression of pluripotency markers, such as OCT3/4, NANOG, SOX2, SSEA1, SSEA4, and AP in immunofluorescence assay, Oct4, Nanog, Sox2, Klf4 and cMyc in RT-PCR. Additionally, single-cell derived bovine iPSCs formed embryoid bodies and teratomas that all subsequently gave rise to differentiated cells from all three embryonic germ layers. The results showed that our reprogramming method could obtain high efficiency single-cell cloning bovine iPSCs, and the efficiency of single cell cloning is 40%.